Unravelling material properties of halide perovskites by combined microwave photoconductivity and time-resolved photoluminescence spectroscopy - Kupfer, Christian; Le Corre, Vincent Marc; Li, Chaohui; Lüer, Larry; Forberich, Karen; Kato, Masashi; Osvet, Andres; Brabec, Christoph (Journal of Materials Chemistry C, 2024)
To take advantage of the huge compositional space of metal halide perovskites, a reliable and fast characterization method is required. By combining time-resolved photoluminescence (trPL) with microwave photoconductivity measurements, we are able to rapidly extract fundamental material properties of promising perovskite materials from bare films. This is achieved by incorporating a rate-equation model into a fitting algorithm based on Bayesian optimization to globally fit the experimental results. Including microwave photoconductivity measurements into our analysis significantly enhances the accuracy of estimating recombination rate constants. Additionally, it grants us the ability to determine the ratio of electron and hole mobilities, a crucial charge transport property that cannot be obtained solely through time-resolved photoluminescence measurements. Furthermore, the high sensitivity of microwave photoconductivity measurements to long-lived trap states yields information about the trap-assisted recombination, which is a major source of efficiency loss for solar devices and is difficult to assess from pure trPL measurements. In this work, we introduce the fundamental principles of microwave photoconductivity, along with the employed rate-equation model and fitting techniques. We then outline the procedure for conducting measurements and extracting the recombination rate constants, trap density, and mobility ratio. Subsequently, we highlight the benefits of combining both methods through a comparison of results from fits using only trPL with those from fits incorporating combined signals on a simulated dataset. We also discuss the merits of conducting intensity-dependent measurements. Finally, we present the annealing-dependent results obtained from a highly relevant triple-cation, mixed-halide perovskite, FA0.82MA0.13Cs0.05Pb(I0.87Br0.13)3, as an application example, where we uncover the presence of long-lived traps beyond 10 μs.
Created from Fastlane, Scopus look-up